Motivation in second language acquisition: A review - Netta, Ayuna (Accentia: Journal of English Language and Education, 2023)
One of the key characteristics that students should possess when learning a second language is motivation. This article elaborates on how important motivation is when learning a second language. Two types of motivation are integrative motivation and instrumental motivation. A desire to encourage students to learn a language for a more practical reason is instrumental motivation. As opposed to this, integrative motivation is the motivating factor behind learning a language brought about by learners' positive attitudes regarding the target language and their eagerness to integrate into the community of that language. Hence, teachers or educators should strongly motivate the students in studying their second language to reach the goals of learning.